Lexicographer, Linguist, Dictionary User: An Uneasy Triangle? - Lombard, F.J. (Lexikos, 1994)
Lexicographer, dictionary user and linguist constitute three important role players in any lexicographical activity. In this presentation they are depicted as three sides or angles of a triangle. Unlike a real mathematical triangle where the three sides always meet, lexicographer, linguist and user are often at loggerheads. Reasons for this phenomenon are ventured and I try to establish whether the lexicographer can reconcile the progressive and ephemeral outlook of linguists with the often conservative needs of users. Ways to reduce the tension between lexicographer, linguist and user are also discussed.